If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -1 = 4x + 15 Reorder the terms: -1 + 12x = 4x + 15 Reorder the terms: -1 + 12x = 15 + 4x Solving -1 + 12x = 15 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + 12x + -4x = 15 + 4x + -4x Combine like terms: 12x + -4x = 8x -1 + 8x = 15 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + 8x = 15 + 0 -1 + 8x = 15 Add '1' to each side of the equation. -1 + 1 + 8x = 15 + 1 Combine like terms: -1 + 1 = 0 0 + 8x = 15 + 1 8x = 15 + 1 Combine like terms: 15 + 1 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| .5n+n=3 | | 2x+4x=-2 | | 5x-60-3x=3(-4x+15)-2 | | 122=2x+2(6x-16) | | f(x)=x^2-x+1 | | -x=99 | | f(x)=(x-3)2 | | 3(12)+6x=4.20(12+x) | | w+w+20p=380m | | 4p+2t=50 | | x/3+6=-45 | | 1.2x-.7x=7.5+1.8 | | 2/3x-7=c | | P=380w+w+20 | | .05n+.1(27+n)=1.90 | | q/36 | | (2x-2)=48 | | 3a-(2a-1)=-2 | | 20y^2-25y+5=0 | | 9x^3-12x^2-15x= | | 10(x-5)=40 | | 8x-y=-7 | | 12(x+8)=24 | | 2(14x-3)=20x+13 | | Y=-x^2+8x-21 | | 31/6*7 | | 4/9(x+18)=24 | | h+1=7 | | x^2-11xy+24y^2=0 | | 1/3(5x-9)=7 | | 2(3x-3)=24 | | 12x^3-15x^2+4x-5=0 |